2020
DOI: 10.1136/bmjdrc-2019-000873
|View full text |Cite
|
Sign up to set email alerts
|

Proinsulin-specific T regulatory cells may control immune responses in type 1 diabetes: implications for adoptive therapy

Abstract: ObjectiveHere we looked for possible mechanisms regulating the progression of type 1 diabetes mellitus (T1DM). In this disease, autoaggressive T cells (T conventional cells, Tconvs) not properly controlled by T regulatory cells (Tregs) destroy pancreatic islets.Research design and methodsWe compared the T-cell compartment of patients with newly diagnosed T1DM (NDT1DM) with long-duration T1DM (LDT1DM) ones. The third group consisted of patients with LDT1DM treated previously with polyclonal Tregs (LDT1DM with T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 31 publications
(37 reference statements)
1
11
0
Order By: Relevance
“…We found that antigen-specific Teffs could be generated with monocytes loaded with antigens, too. These results are important as they confirmed our in vivo data from type 1 diabetes in which we found that the disease-specific antigens can induce both specific Tregs and Teffs and the balance between these two subsets might be associated with the course of the disease (22). Importantly, current report confirms in vitro that the whole insulin is a poor stimulator of Tregs and the efficient induction of tolerance should be performed with other peptides, like b chain peptide 9-23.…”
Section: Discussionsupporting
confidence: 88%
“…We found that antigen-specific Teffs could be generated with monocytes loaded with antigens, too. These results are important as they confirmed our in vivo data from type 1 diabetes in which we found that the disease-specific antigens can induce both specific Tregs and Teffs and the balance between these two subsets might be associated with the course of the disease (22). Importantly, current report confirms in vitro that the whole insulin is a poor stimulator of Tregs and the efficient induction of tolerance should be performed with other peptides, like b chain peptide 9-23.…”
Section: Discussionsupporting
confidence: 88%
“… 114 The complexity of the response is also caused by the fact that the same epitopes can trigger responses in both Tregs and Tconvs, and the final outcome depends on which subset prevails. 118 Nevertheless, there have been attempts to create Tregs with engineered TCRs to direct them to particular sites and protect particular organs from autoimmune attack. 119 These attempts for MS are at the EAE stage.…”
Section: Cell-based Tolerogenic Therapiesmentioning
confidence: 99%
“…In the context of diabetes, both CAR T cell and regulatory T cell (Tregs)-based treatments are currently being developed (141)(142)(143)(144)(145)(146). Under normal conditions, Tregs mediate immune tolerance by expressing anti-inflammatory cytokines and dampening the inflammatory or cytotoxic responses of other types of T lymphocytes (147).…”
Section: Cell Therapy As a Promising Treatment For More Complex Diseasesmentioning
confidence: 99%